Técnicas para tratar enfermedades capilares y su incidencia en el proceso de enseñanza aprendizaje de la asignatura de belleza y cosmetología de los estudiantes del centro artesanal particular cinco de noviembre del cantón Naranjal, provincia Guayas. - Tuapante Rivas, Rita Nieves (2017)
The scalp is a part of our body that like all, needs our care. Although you do not believe it, there are many diseases that attack it, even silently, so we need to be informed to avoid getting sick, knowing the causes and the way to treat them so that we can finally fight them. Sometimes the use of many chemicals cause conditions to our hair, as well as not using an appropriate shampoo. There are diseases that develop on the scalp, which can generate a slow process of hair growth and even worse, can cause accelerated hair loss, either temporarily or otherwise, permanent. There are diseases in the scalp that can affect hair growth, causing it to fall temporarily or permanently. A distinction should be made between the conditions of the scalp, making a diagnosis as accurate as possible thanks to the timely intervention of a competent professional. Scalp diseases are those that are acquired due to germs and other microorganisms that affect the bark where the hair is born and can cause problems when applying a treatment. Being informed about these capillary problems, knowing their causes and knowing how to treat them allows us to have all the necessary tools to combat them without neglecting the health and aesthetics of hair. Hair diseases can affect the normal growth of our hair and even cause the hair to fall momentarily or even permanently.